2016
DOI: 10.18632/oncotarget.10048
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of lysine acetylation in cancer: prognostic biomarker and therapeutic target

Abstract: Lysine acetylation is a post-translational modification that regulates gene transcription by targeting histones as well as a variety of transcription factors in the nucleus. Recently, several reports have demonstrated that numerous cytosolic proteins are also acetylated and that this modification, affecting protein activity, localization and stability has profound consequences on their cellular functions. Interestingly, most non-histone proteins targeted by acetylation are relevant for tumorigenesis. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 167 publications
(183 reference statements)
0
61
0
Order By: Relevance
“…Lysine acetylation is a dynamic process that can be modulated within minutes and it is regulated in histone and non-histone proteins by the redundant activity of KATs. Therefore, cancer cells may rapidly recover from incomplete pharmacological inhibition or from the specific inhibition of a particular KAT (53). Here, we showed that proscillaridin treatment in MYC overexpressing leukemia cells, led to the downregulation of several KATs, produced MYC inhibition, and induced persistent leukemia cell differentiation, which was maintained for several days after drug removal.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Lysine acetylation is a dynamic process that can be modulated within minutes and it is regulated in histone and non-histone proteins by the redundant activity of KATs. Therefore, cancer cells may rapidly recover from incomplete pharmacological inhibition or from the specific inhibition of a particular KAT (53). Here, we showed that proscillaridin treatment in MYC overexpressing leukemia cells, led to the downregulation of several KATs, produced MYC inhibition, and induced persistent leukemia cell differentiation, which was maintained for several days after drug removal.…”
Section: Discussionmentioning
confidence: 83%
“…Significant reduction in KAT protein expression including KAT2A, KAT3A, KAT3B and KAT6A, which target histone H3, occurred 8h before significant H3 acetylation loss described previously (Figure 4a). Despite KAT5 decrease, a KAT known to acetylate both H3 and H4, no changes in H4 acetylation (total or on specific lysines) were measured after treatment (Supplemental Figure 4a) (53)(54)(55)(56)(57). These results can be explained by the fact that KAT7 (HBO1) expression, which is also involved in H4 acetylation, was not affected by the treatment (58,59).…”
Section: Proscillaridin Downregulates Histone Acetyltransferases Invomentioning
confidence: 89%
“…These defects can be reversed by restoring αK40 acetylation levels 17 . On the other hand, elevated levels of αK40 acetylation promote cell-cell aggregation, migration and tumor reattachment in multiple aggressive, metastatic breast cancer cell lines 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Acetylation is an important protein posttranslational modification that was first found on histones. A large number of nonhistone modifications has been found in many species, such as humans (Li et al., ), mice (Nallamilli et al., ), and B. mori (Zhou et al., ), playing important biological and physiological functions, such as regulation of tumorigenesis (Di Martile, Del Bufalo, & Trisciuoglio, ), lipid biosynthesis (Wang, Guo, Liang, Chi, & Liu, ), and rescue of inflammation (Qin et al., ). Protein acetylation is catalyzed by acetyltransferase.…”
Section: Discussionmentioning
confidence: 99%